Politics in India/edited by M. M. Sankhdher and Gurdeep Kaur - "Sankhdher, M. M. (ed.)" (New Delhi, 2005)
The present book on Indian polity is a product of the confined effort of research scholars.the divided into three parts. Part 1 Politics in Ancient India;Part 2 Politics of change and politics thought; Part 3 Politics in modern India.
Keywords: Political science-India